2018
DOI: 10.1104/pp.18.00324
|View full text |Cite
|
Sign up to set email alerts
|

INDETERMINATE SPIKELET1 Recruits Histone Deacetylase and a Transcriptional Repression Complex to Regulate Rice Salt Tolerance

Abstract: Perception and transduction of salt stress signals are critical for plant survival, growth, and propagation. Thus, identification of components of the salt stress-signaling pathway is important for rice () molecular breeding of salt stress resistance. Here, we report the identification of an apetala2/ethylene response factor transcription factor INDETERMINATE SPIKELET1 (IDS1) and its roles in the regulation of rice salt tolerance. By genetic screening and phenotype analysis, we demonstrated that IDS1 conferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…Two rice AP2 genes, supernumerary bract ( SNB ) and OsIDS1 , synergistically control inflorescence architecture and floral meristem establishment (Lee and An, ). SNB and OsIDS1 also regulate lodicule development and rice salt tolerance (Cheng et al , ). A most recent study also showed that SNB controls rice seed shattering and seed size (Jiang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Two rice AP2 genes, supernumerary bract ( SNB ) and OsIDS1 , synergistically control inflorescence architecture and floral meristem establishment (Lee and An, ). SNB and OsIDS1 also regulate lodicule development and rice salt tolerance (Cheng et al , ). A most recent study also showed that SNB controls rice seed shattering and seed size (Jiang et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Site specificity of HDACs on histones has not been clearly demonstrated. Alteration of rice HDT701 expression level affects global H4K5 and H4K16 acetylation levels, while many HDACs regulates H3 acetylation at specific genes (Ding et al, 2012; Zheng et al, 2016; Liu et al, 2017; Ueda et al, 2017; Wang et al, 2017; Cheng et al, 2018; Park et al, 2018). In addition to histones, non-histone substrates of plant RPD3/HDA1 family HDACs has also been identified (Hartl et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…overexpression of HDA702 enhances growth rate, alters plant architecture [64], and increases root growth through deacetylating OsNAC6 locus [65]. HDA702 implicates in formation of IDS1-TPR1-HDA1 transcriptional repression complex, contributing to negative regulation of salt tolerance [66]. These data suggest that HDA702/703/710 in rice may have divergent developmental functions compared with closely related homologs in Arabidopsis.…”
Section: Hdac: Prd3/hda1 Familymentioning
confidence: 88%